The basic concept of baluwarti Cirebon palace, Study case of Kasepuhan, Kanoman and Kacirebon Palace (ARTEKS : Jurnal Teknik Arsitektur, 2021)
Cirebon is a unique city with 3 palaces, including Kasepuhan, Kanoman, Kacirebonan. The palaces are influenced by the history and culture of the Baluwarti palace, which is believed to have specific concepts in the arrangement and placement of building masses. This study  examines the concepts underlying Baluwarti in the 3 Cirebon palaces. This is achieved by first studying the basis of Palace's trust rules used to regulate the mass placing of the palace building. Subsequently, the study uses an architectural anatomical theory consisting of the building site and scope, and the property-composition theory to explore the orientation and position of the Palace building. The results showed that the concept underlying Baluwarti in the 3 Cirebon palaces consists of Javanese and Sundanese cosmologies as building orientation, the type of land on which it was built, and Mahameru and the building position. This research contributes to the general architecture in the uniqueness of historical, cultural and local values. Also, it provides architectural information regarding the concepts underlying Baluwarti in the 3 Cirebon palaces.
Keywords: Anatomy architecture; Baluwarti Cirebon Palace; Mahameru; Property-composition; Sundanese-Javanese cosmology